Expression of the Excitatory Postsynaptic Scaffolding Protein, Shank3, in Human Brain: Effect of Age and Alzheimer’s Disease - Wan, Lily; Ai, Jia-Qi; Yang, Chen; Jiang, Juan; Zhang, Qi-Lei; Luo, Zhao-Hui; Huang, Rou-Jie; Tu, Tian; Pan, Aihua; Tu, Ewen; Manavis, Jim; Xiao, Bo; et al. (Frontiers in Aging Neuroscience, 2021)
Shank3 is a postsynaptic scaffolding protein of excitatory synapses. Mutations or variations of SHANK3 are associated with various psychiatric and neurological disorders. We set to determine its normal expression pattern in human brain, and its change, if any, with age and Alzheimer’s disease (AD)-type β-amyloid (Aβ) and Tau pathogenesis. In general, Shank3 immunoreactivity (IR) exhibited largely a neuropil pattern with differential laminar/regional distribution across brain regions. In youth and adults, subsets of pyramidal/multipolar neurons in the cerebrum, striatum and thalamus showed moderate IR, while some large-sized neurons in the brainstem and the granule cells in the cerebellar cortex exhibited light IR. In double immunofluorescence, Shank3 IR occurred at the sublemmal regions in neuronal somata and large dendrites, apposing to synaptophysin-labeled presynaptic terminals. In aged cases, immunolabeled neuronal somata were reduced, with a disrupted neuropil labeling seen in the molecular layer of the dentate gyrus in AD cases. In immunoblot, levels of Shank3 protein were positively correlated with that of the postsynaptic density protein 95 (PSD95) among different brain regions. Levels of Shank3, PSD95 and synaptophysin immunoblotted in the prefrontal, precentral and cerebellar cortical lysates were reduced in the aged and AD relative to youth and adult groups. Taken together, the differential Shank3 expression among brain structures/regions indicate varied local density of the excitatory synapses. The enriched Shank3 expression in the forebrain subregions appears in consistent with a role of this protein in modulation of high cognitive functions. The decline of its expression in aged and AD brains may relate to the degeneration excitatory synapses.